2020
DOI: 10.1038/s41398-020-0740-y
|View full text |Cite
|
Sign up to set email alerts
|

Shared and distinct resting functional connectivity in children and adults with attention-deficit/hyperactivity disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) often persists into adulthood, with a shift of symptoms including less hyperactivity/impulsivity and more co-morbidity of affective disorders in ADHD adult . Many studies have questioned the stability in diagnosing of ADHD from childhood to adulthood, and the shared and distinct aberrant functional connectivities (FCs) between ADHD child and ADHD adult remain unidentified. We aim to explore shared and distinct FC patterns in ADHD child and ADHD adult , and furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 50 publications
(42 reference statements)
4
29
1
3
Order By: Relevance
“…Alterations in brain structure, connectivity, and maturation processes in patients with ADHD have been reported [18][19][20][21][22] . Particularly, a delay in cerebral cortex maturation predominantly in the frontal cortex has been noted in ADHD patients 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in brain structure, connectivity, and maturation processes in patients with ADHD have been reported [18][19][20][21][22] . Particularly, a delay in cerebral cortex maturation predominantly in the frontal cortex has been noted in ADHD patients 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued more recently (Michelini et al, 2019) that atypical task-based functional connectivity in individuals with childhood ADHD may persist into adulthood. Taken together, these findings suggest that a neural signature of ADHD may be found within taskbased functional connectivity from the go/no-go task, even from young adults, advancing this approach as a potential detector of biomarkers that may address the poor stability of ADHD diagnosis (Guo et al, 2020).…”
Section: Neural Circuitry Implicated In Attention Disordersmentioning
confidence: 86%
“…The difference in classification performance between our study and these earlier studies suggests that, though summary metrics quantifying connectivity motifs in core functional networks are predictive of ADHD, information about specific connections provides a great deal of additional diagnostic information. Guo et al (2020) demonstrated that SVM classifiers were able to identify ADHD male adults from rs-fMRI connectivity measured among ADHD children with 76% accuracy, after first selecting the top 2% of diagnostic features from alternative modelssimilar to the feature reduction step employed in the present study. The authors argue that, though the predictive features may vary somewhat across cohort, the reasonable cross-cohort performance suggests that resting state functional connectivity may be a developmentally stable biomarker of ADHD.…”
Section: Relation To Previous Workmentioning
confidence: 88%
“…Functional and structural abnormalities of the precentral gyrus are common in ADHD studies. In a recent resting-state functional connectivity study of ADHD, Guo also used whole-brain functional connectivity to classify features for machine learning and found that two of the four features with the best discriminability were related to the precentral gyrus, namely the precentral gyrus-prefrontal lobe and the precentral gyrus-superior temporal gyrus (Guo et al, 2020). In a young adult with ADHD, Krista found that the cerebral cortex thickness of the precentral and postcentral gyrus was the only brain regions associated with the persistence of ADHD, and the cluster in the precentral gyrus was close to that of DICCCOL 175 (Lisdahl et al, 2016).…”
Section: Discussionmentioning
confidence: 99%